Negotiating clerical identities : priests, monks and masculinity in the Middle Ages - Thibodeaux, Jennifer D. (Genders and sexualities in history., 2010)
Was a medieval priest viewed as masculine by his parishioners? Did a monk consider himself fully male? How did a bishop assert his masculinity in conflicts with secular authorities? These are some of the questions posed by Negotiating Clerical Identities: Priests, Monks and Masculinity in the Middle Ages. In this volume, Jennifer Thibodeaux has assembled the most cutting-edge research today on medieval clerics and masculine performances. Spanning a wide range of geographical contexts and time periods, the essays in this volume illuminate the ways in which medieval clerics performed masculinity and negotiated their gender identities, with both lay society and within the various orders of the medieval Church.